1993
DOI: 10.1113/jphysiol.1993.sp019563
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐dependent regulation of epithelial sodium channel densities in frog skin; a role for the cytoskeleton.

Abstract: SUMMARY1. A weak electroneutral sodium channel blocker 6-chloro-3,5-diamino-pyrazine-2-carboxamide was used to perform noise analysis on isolated epithelium from Rana fuscigula to determine the cellular mechanism underlying autoregulation of Na+ channel densities in response to a reduction in the mucosal Na+ concentration.2. The inherent transport rates of these tissues were generally lower than in other frog skins. and to a lesser extent by an increase in NT, the total number of open and closed channels. 5. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Frog skin epithelium offers the opportunity to study the structure-function refationship of the Na+ transport pathway in a population of cells that is a target for the natrifet-ic actions of AVP, while uncomplicated by an effect on membrane water permeability. We have used two methods to reveal the distribution of F-actin in the granular cells in frog skin, where they may beinvolved in the regulation of Na+ channels [6]. Immutiofluorescence revealed that actin was mainly concentrated as a diffuse band beneath the plasma membrane with little evi dence for it in the central areas.…”
Section: Lmmunogold Labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Frog skin epithelium offers the opportunity to study the structure-function refationship of the Na+ transport pathway in a population of cells that is a target for the natrifet-ic actions of AVP, while uncomplicated by an effect on membrane water permeability. We have used two methods to reveal the distribution of F-actin in the granular cells in frog skin, where they may beinvolved in the regulation of Na+ channels [6]. Immutiofluorescence revealed that actin was mainly concentrated as a diffuse band beneath the plasma membrane with little evi dence for it in the central areas.…”
Section: Lmmunogold Labellingmentioning
confidence: 99%
“…Of current interest is increasing evidence suggesting that in Na+-transporting epithelia, regulation of Na+ channel activity may involve interactions with the actin network [3,25,281. In this regard, recent studies have shown that an intact actin network is essential for maintaining epithelial sodium reabsorption in the rat renal tubule [16] while treating frog skin with cytochalasin B (CB) inhibits the autoregulatory increase in the number of open Na+ channels in response to a decrease in luminal sodium concentration [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have suggested an association between the epithelial Na+ channel and the cytoskeleton. Disruption of actin microfilaments, addition of actin fragments or actin-gelsolin complexes alter Na+ channel activity in A6 cells (Cantiello et al, 1991) and impair Na+ channel regulation in frog skin (Els and Chou, 1993). In addition, a decrease in Na+ transport and number of apical membrane Na+ channels in alveolar epithelial cells has been shown to be associated with disruption of the actin cytoskeletal network (Compeau et al, 1994).…”
mentioning
confidence: 99%
“…Most of these investigations were carried out using different cells treated with cytochalasin. The influence of cytochalasin on the intracellular potential due to cell deformation depends on the dose, exposure time, and type of cells (Els and Chou, 1993;Isenberg et al, 2003;Guharay and Sachs, 1984;Kamkin et al, 2003a, b;Kim, 1993;Karpushev et al, 2010;Wang et al, 2002;Zhang et al, 2000). Cytochalasin results in the reduction of cortex network density down to its destruction, in the decrease of cortex elasticity and as a consequence, the decrease of membrane stiffness (Byfield et al, 2004;Rotsch et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Thus partial or full suppression of MEC after cortex removal was found using the patch-clamp method (Zhang et al, 2000). The necessity of the cytoskeleton for MET realization was shown in a large number of investigations based on the use of cytochalasin (Els and Chou, 1993;Isenberg et al, 2003;Kamkin et al, 2003a, b;Karpushev et al, 2010;Wang et al, 2002). Cytochalasins are a group of fungal metabolites.…”
Section: Introductionmentioning
confidence: 95%